Apuntes de soteriología (Teología, 2020)
The author offers some “notes” on soteriological theology from different authors, with the purpose of placing the reader in the problems of today. The pastoral scope of soteriological categories is because they transmit a certain image of God. For example, in the nineteenth century and part of the twentieth century the image of cruel satisfaction or sacrifice understood as slaughter or bloodshed dominate the scene of the preaching of Lent and Easter. With theological and pastoral sense, the presentation limits itself to the essential core of the doctrine contained in the soteriological categories selected.
Keywords: Soteriological Theology; Christology; Image of God; Preaching